EXPERIMENTAL STUDY ON TENSILE PROPERTIES OF HUCK RIVET JOINT - ZHANG XiangFeng; QIN Nan; WANG YongYan (Jixie qiangdu)
Aiming at the phenomenon that the Huck rivet often falls off in the application of rolling stock,the quasi-static tensile test of Huck rivet was carried out by using the universal mechanical testing machine. The tensile performance curve of Huck rivet is obtained. The failure process of the riveting part is divided into five stages according to the test phenomenon and the drawing performance curve. In addition,the failure load of the friction pairs and the shear behavior of the rivet and the maximum shear resistance are obtained. After that,the quasi-static tensile test was carried out on the Huck rivet of the fatigue test under low stress and low cycle times,we can found that in the second half of the Huck rivet shear performance curve,there is a trend of instantaneous load reduction,but it has little effect on the maximum shear strength. The failure process is divided into four stages according to the performance curve. In order to improve the design of rivet joint and the fatigue test of Huck rivet.